Effect of Incentives Based Two Factor Theory on Employee Performance in Telecom Sector of Pakistan - Khan, A. A.; Abbas, N.; Zaki, K. A. (The Nucleus, 2017)
Motivated employees are the building block of any successful organization. This study is executed to analyze the relationship between Incentive system and employee performance in Telecom Sector of Pakistan. The theoretical framework of this research is based on the effect of Two Factor Theory on employee performance i-e motivation factors and hygiene factors. Employees of different telecom sector departments were being focused through the detailed survey by making use of questionnaire. The results of research show that incentive systems have significant impact on employees’ performance. This research is presented in structured way to help practitioners to analyze the factors that may help them to enhance their employees’ performance.